Politicization of the broadcast media: an examination of 2015 general elections in Nigeria - Bashir, Muktar; Mohd Sani, Mohd Azizuddin; Ahmad Zakuan, Ummu Atiyah (Society of Scientific Research and Education (SSRE), 2018)
There cannot be democracy without elections, nor can there be elections without the presence of vibrant media. They are constitutionally responsible to educate the populace with up to date information that is qualitative in nature to transform them into meaningful mindsets for better participation. However, the way and manner the media conducts its affairs during the 2015 general elections in Nigeria necessitates the need for this paper. The paper examines the nature and character of the broadcast media on the 2015 general elections in Nigeria. Authoritarian theory of communication is employed to set the pace. The paper utilizes secondary source as a method of data collection. It concludes that broadcast media have been politicized to a large extent during the 2015 general elections in Nigeria, reporting unethical issues and attacking the personality of the opposition candidates which is against the journalistic best practices across the globe. The paper recommends that the media should be professional in the discharge of its social responsibility in educating the people with truthful information without fair or favor. This will no doubt equip them with qualitative information to make informed choices during the electioneering activity, thereby, improving the quality of the elections in particular and democracy in general.